Exploring the potential of triticale lines for bioethanol production - Latini, Arianna; Cantale, Cristina; Gazza, Laura; Nocente, Francesca; Migliore, Giada; Maccioni, Oliviero; Marconi, Ombretta; Floridi, Simona; De Francesco, Giovanni; Ammar, Karim; Galeffi, Patrizia (Open Exploration Publishing, 2024)
Aim: Triticale is a well adaptable crop, tolerant of disease and abiotic stresses, and able to grow with good yields even in poor soil, thus representing a good choice to develop a new industrial agri-chain in Italy in a sustainability contest, to cope with its soil problems due to incoming desertification. Methods: Two triticale elite lines were grown in marginal lands in controlled field experiments. The lines were harvested at two different development stages, namely green mass and seeds, and suitable standard protocols were applied to test their potential to produce bioethanol in line with the emerging bioenergy processes. Results: The protocols applied were able to obtain bioethanol with a good yield from both feedstocks. In particular, very efficient fermentation kinetics was observed using seed feedstock, with a sharp curve between 15 h and 24 h, reaching 84% of the total alcohol obtained (final time 72 h). Conclusions: Therefore, the results of this research point to new sustainable potential for industrial applications of triticale crops in Italy. Furthermore, the high activity of the endogenous amylolytic enzymes, mainly α-amylase, and the high starch content suggest the potential use of triticale in other industrial applications, like the brewing industry.